Sistem Penunjang Keputusan Penilaian Karyawan Terbaik Berbasis Metode Profile Matching Pada PT. Aplikasi Digital Kreatif - Annisa Tsamratul 'Ain (Nindikayla Institute, 2025)
Aplikasi Digital Kreatif is a company engaged in the creative and digital industry, where human resource quality plays a vital role in supporting productivity, innovation, and organizational performance. The main problem faced by the company is that the employee performance assessment process is still conducted semi-manually using Microsoft Excel and Google Drive. This condition causes slow data recapitulation, a high risk of input errors, difficulty in retrieving historical data, and less objective assessment results due to the absence of standardized weighting and ranking mechanisms. This study aims to design a web-based decision support system using the Profile Matching method to determine the best employee. The Profile Matching method is applied by comparing employees’ actual profiles with ideal profiles based on criteria and subcriteria determined by the company. The research stages include data collection, data analysis, problem identification, decision support system design, and prototype development. The results show that the proposed system can manage employee data, assessment periods, criteria, subcriteria, scores, gap calculation, gap weighting, core factor and secondary factor calculation, total aspect scores, and automatic ranking. The calculation results produce a structured and objective ranking of the best employees. The system is expected to assist company leaders in accelerating performance evaluation, reducing subjectivity, and supporting data-driven decision-making.